Archaeology’s Offerings to Jesuit History - Cobb, Charles R. (Journal of Jesuit studies, 2021)
Abstract The contributions to the thematic issue of this journal address archaeological approaches to Jesuit missionizing in three contexts in the colonial Americas: substantial missions that also served as plantations, missions lacking full-time clergy, and short-term outposts on the edges of colonial empires. By relying on evidence from the landscape, the built environment, and objects, these studies demonstrate that the Jesuit enterprise was not subservient to, or a simple accomplice of, European colonial ambitions. Instead, missionizing by all Christian orders was intertwined with an evolution of both secular and religious philosophies that gave rise to modernity.